A study on atmospheric pressure plasma jet for hospital acquired bacterial inactivation by different working gases with varying flow rate and exposure time
Atmospheric Pressure Plasma Jet (APPJ) is ionized gas that is generated at atmospheric pressure and at room temperature, by allowing the gas to flow in a small tube with the higher voltage supplied to the area. Plasma offers many advantages that makes it suitable in various applications, including medicine and sterilization. This research focuses on a cold plasma application, namely APPJ, in the sterilization field. The objective of this study is to establish the plasma for the inactivation of bacteria, to study the microbial inactivation effects of APPJ variables in term of the types of microbes, the types of gases, the various gas flow rates, and the exposure times, to study the optical emission spectrum of the APPJ, and to observe the bacteria after exposure to plasma by high power microscope. In this study, a self-developed APPJ was used to inactivate Acinetobacter baumannii (A.baumannii) and Methicillin-resistant Staphylococcus aureus (MRSA) by using different gases, namely He, He/N, and Ar at various gas flow rates in the range of 300ml/min to 1000ml/min, for 9, 12, 15, and 18 seconds of exposure. After that, the treated samples were transferred to a new agar surface and incubated for 24 hours at 37◦C to observe bacterial growth. The A.baumannii and the MRSA were successfully inactivated by the APPJ. The He plasma inactivated the bacteria more effectively than the other gases. The A.baumannii and the MRSA bacteria were fully inactivated after 9 and 12 seconds, respectively, at the flow rate of 1000ml/min. Ar plasma achieved 0% survival at 9s exposure, however the inactivation of bacteria were not consistent especially for MRSA.